Wilbur H. Durborough memoir and literary manuscript - Durborough, Wilbur H. (Wilbur Henry), 1882-1946.
Durborough's memoir; a fictionalized account of Durborough's years as a young man in Philadelphia, Pa., and his employment as an oiler on the steamship Manatawa; and a preservation photocopy of the account. The memoir covers the years 1913-1917 and documents his work as a photographer for the Newspaper Enterprise Association traveling to Mexico in 1913 to photograph and film the Mexican Revolution where he interviewed Pancho Villa and met Rodolfo Fierro and Salvador Mercado. Also documents his work photographing and filming the German war effort on the Eastern Front in 1914. Durborough addresses the role the Democratic National Committee (U.S.) played in the distribution of the film that was released in 1915 under the title On the Firing Line with the Germans. Also covers his return to America and subsequent work as a newspaper correspondent and photographer in Chicago, Ill.
Photographer, cinematographer, and journalist.
Collection material in English.
Keywords: Mercado, Salvador; Fierro, Rodolfo, -- 1880-1915.; Villa, Pancho, -- 1878-1923.; Democratic National Committee (U.S.); Newspaper Enterprise Association; Manatawa (Steamship); Journalism -- Illinois -- Chicago; Photography -- Europe; Photography -- Illinois -- Chicago; Photography -- Mexico; Sea stories; World War, 1914-1918 -- Campaigns -- Eastern Front; World War, 1914-1918 -- Motion pictures and the war; World War, 1914-1918 -- Germany; Mexico -- Description and travel; Mexico -- History -- Revolution, 1910-1920.; Philadelphia (Pa.) -- Social life and customs; Cinematographers; Journalists; Photographers